Little red book of effective speaking skills - O'Brien, Terry (Rupa Publications, 2011)
Listening, Speaking, Reading and Writing: The 2 of the 4 essential skills for communication: Speaking. All you need for honing your Speaking Skills are the 3Ss: o Courage is what it takes to stand up and speak; courage is also what it takes to sit down and listen. o Speech is power: speech is to persuade, to convert, to compel.